Geochemistry of Small Canadian Arctic Rivers with Diverse Geological and Hydrological Settings. Issue 1 (21st January 2020) - Brown, Kristina A.; Williams, William J.; Carmack, Eddy C.; Fiske, Greg; François, Roger; McLennan, Donald; Peucker‐Ehrenbrink, Bernhard
Abstract: A survey of 25 coastal‐draining rivers across the Canadian Arctic Archipelago (CAA) shows that these systems are distinct from the largest Arctic rivers that drain watersheds extending far south of the Arctic circle. Observations collected from 2014 to 2016 illustrate the influences of seasonal hydrology, bedrock geology, and landscape physiography on each river's inorganic geochemical characteristics. Summertime data show the impact of coincident gradients in lake cover and surficial geology on river geochemical signatures. In the north and central CAA, drainage basins are generally smaller, underlain by sedimentary bedrock, and their hydrology is driven by seasonal precipitation pulses that undergo little modification before they enter the coastal ocean. In the southern CAA, a high density of lakes stores water longer within the terrestrial system, permitting more modification of water isotope and geochemical characteristics. Annual time‐series observations from two CAA rivers reveal that their concentration‐discharge relationships differ compared with those of the largest Arctic rivers, suggesting that future projections of dissolved ion fluxes from CAA rivers to the Arctic Ocean may not be reliably made based on compositions of the largest Arctic rivers alone, and that rivers draining the CAA region will likely follow different trajectories of change under a warming climate. Understanding how these small, coastal‐draining river systems will respond to climate change is essential to fully evaluate the impact of changing freshwater inputs to the Arctic marine system. Plain Language Summary: River inputs are important for the physics and biogeochemistry of the rapidly changing Arctic Ocean. Most of our knowledge of river inputs comes from studies of the six largest rivers which drain areas reaching far south of the Arctic Circle, omitting 45% of the pan‐Arctic watershed. This has left a gap in our understanding of smaller, coastal‐draining rivers and how these are influenced by the changing climate. We studied 25 coastal‐draining rivers in the Canadian Arctic Archipelago (CAA) for geochemical comparison to the larger, more southerly rivers. Summertime survey data show that geochemical properties change from south to north following the distribution of lake cover, bedrock geology, and glacial history. Unlike the largest Arctic rivers, however, repeat observations over the annual cycle indicate that dissolved ion concentrations are not strongly influenced by changing water fluxes in the CAA region. To fully understand the impact of changing freshwater inputs to the Arctic Ocean requires consideration of smaller watersheds that may change differently compared to the largest Arctic rivers. Key Points: Geochemical characteristics of Canadian Arctic Archipelago rivers reflect geological and hydrological heterogeneity across the region Time‐series observations from two CAA rivers reveal weak, positive concentration‐discharge relationships Major ion characteristics of CAA rivers are similar to large Arctic rivers, but their response to future change will likely differ